Covid-19: Protecting lives and livelihoods - Lee, Pei May (2020)
After more than one month of Movement Control Order (MCO), Prime Minister Tan Sri Muhyiddin Yassin announced a partial lifting to Conditional MCO (CMCO) to allow some economic sectors to operate. Companies, however, must adhere to the standard operating procedures (SOPs) outlined by the Ministry of Health, leading to mixed reactions. On one hand, business owners were happy with the decision allowing them to resume operations while another segment of society feels that the decision may cause another wave of infections.